The Enhanced M-GEAR Protocol for Wireless Sensor Network LifeTime - Kaur, Amandeep; Singh, Sukhbeer; Chouhan, Neelam (International Journal of Computer Sciences and Engineering, 2019)
The enhancement of life time in a WSN mainly focus on the clustering and energy of nodes. The concern to select the cluster head in a network works on different techniques, the region based energy efficient technique for the data communication among nodes is one of them in a wireless sensor network. This paper focus on the region based called gateway based energy-efficient routing protocol. This paper mainly focus on distance based cluster head selection and the communication among region nodes with the base station depends upon the positive coordinates of the region following the base station.